Invited review: strategic adoption of antibiotic-free pork production: the importance of a holistic approach. Issue 3 (16th May 2022) - Patience, John F; Ramirez, Alejandro
Abstract: The discovery of the use of antibiotics to enhance growth in the 1950s proved to be one of the most dramatic and influential in the history of animal agriculture. Antibiotics have served animal agriculture, as well as human and animal medicine, well for more than seven decades, but emerging from this tremendous success has been the phenomenon of antimicrobial resistance. Consequently, human medicine and animal agriculture are being called upon, through legislation and/or marketplace demands, to reduce or eliminate antibiotics as growth promotants and even as therapeutics. As explained in this review, adoption of antibiotic-free (ABF ) pork production would represent a sea change. By identifying key areas requiring attention, the clear message of this review is that success with ABF production, also referred to as "no antibiotics ever, " demands a multifaceted and multidisciplinary approach. Too frequently, the topic has been approached in a piecemeal fashion by considering only one aspect of production, such as the use of certain feed additives or the adjustment in health management. Based on the literature and on practical experience, a more holistic approach is essential. It will require the modification of diet formulations to not only provide essential nutrients and energy, but to also maximize the effectiveness of normal immunological and physiological capabilities that support good health. It must also include the selection of effective non-antibiotic feed additives along with functional ingredients that have been shown to improve the utility and architecture of the gastrointestinal tract, to improve the microbiome, and to support the immune system. This holistic approach will require refining animal management strategies, including selection for more robust genetics, greater focus on care during the particularly sensitive perinatal and post-weaning periods, and practices that minimize social and environmental stressors. A clear strategy is needed to reduce pathogen load in the barn, such as greater emphasis on hygiene and biosecurity, adoption of a strategic vaccine program and the universal adoption of all-in-all-out housing. Of course, overall health management of the herd, as well as the details of animal flows, cannot be ignored. These management areas will support the basic biology of the pig in avoiding or, where necessary, overcoming pathogen challenges without the need for antibiotics, or at least with reduced usage. Lay Summary: Antimicrobial resistance experienced in human and animal medicine has led to reductions in the use of antibiotics in pork production. This has meant the widespread elimination of the use of antibiotics as growth promotants and greater restrictions on antibiotics used in human medicine. A small but growing number of pork producers are adopting so-called antibiotic-free systems, where pigs receive no antibiotics during their lifetime. Yet, farmers' first priority is to protect the health and well-being of their pigs, and even in antibiotic-free systems, some animals will require medical treatment. To achieve success in antibiotic-free production, it is essential that a holistic approach be adopted: 1) selection of effective non-antibiotic feed additives that help maintain good health and assist the pig in resisting illness when infection does occur, 2) modifying diet formulations to not only provide essential nutrients and energy, but also support the effectiveness of normal immunological and physiology mechanisms to encourage good health and to resist pathogens, 3) a critical focus on the social, environmental and physical environment in which the pig lives to minimize stressors, and 4) enhanced hygiene, biosecurity, and disease management. Abstract : Adoption of antibiotic-free pork production is a very demanding strategy that requires a holistic approach to achieve success. This will include selecting effective non-antibiotic feed additives, modifying diet formulations to support normal immunological and physiology mechanisms, minimizing physical, social, and environmental stressors, and enhancing hygiene, biosecurity, and disease management.